Questão ambiental e a produção do conhecimento em Serviço Social - Carmona, Rafael Garcia (2023)
In contemporary times, it is possible to identify a structural crisis of capital, which has destroyed work and nature, thus generating the so-called environmental crisis. The eagerness for profitability made the capitalists take natural goods in their integral form, to the point of not worrying about their disappearance. The analytical perspective adopted comprises not only issues related to the use of the natural environment, but also social relations, which unequally translate into the production of space and how the negative consequences of these forms of appropriation are imposed unequally between classes and groups. social. In this sense, the environmental issue condenses the contradiction of the capitalist mode of production and its impacts on natural resources and life in society. This conception present in social reality requires the social work profession to unveil the constitutive elements and build professional responses. Thus, this thesis aims to analyze how the environmental issue is presented in recent academic productions of Social Work. For this, its specific objectives are: to understand the constitutive elements of the environmental issue; discuss Marxian thought and Marxist thinkers, in order to highlight the relevance of this theoretical perspective for the analysis of the environmental issue; and highlight the main trends in scientific productions produced by social workers. The methodology used consisted of exploratory bibliographical and documental research. As sources for the bibliographic research, it was chosen to select three magazines in the area of Social Work, Qualis A1 evaluation, according to the Coordination for the Improvement of Higher Education Personnel (CAPES): Revista Katálysis, Revista de Políticas Públicas and Revista Serviço Social e Sociedade. The research had publications between the years 2018 and 2022 as a temporal cut. With regard to the foundations presented in research on the environmental issue, the conception linked to the analysis of the reproduction of capital, a reflection of anthropic activity and the junction of of societynature. However, most productions lack a more precise concept of the environmental issue. It was also identified that a large part of the academic production of the last five years deals with the theme, locating the debate around elements of analysis of social reality and less on elements that involve professional work. Finally, it is emphasized that there is no overcoming of capital without facing the question of the social metabolic relationship with nature; the devastation of natural assets experienced by humanity must be faced with resistance and with the construction of another sociability